TO THE PROBLEM OF THE DYNAMICS OF GROUND ATMOSPHERE - Draganov, B. (Energy and Automation, 2016)
Shows the system of equations for the dynamics of the main characteristics of the atmosphere and surface conditions the probability of sustainability. These distinctive features boundary layer.